Genetic Dissection of a Super Enhancer Controlling the Nppa-Nppb Cluster in the Heart. Issue 1 (8th January 2021) - Man, Joyce C.K.; van Duijvenboden, Karel; Krijger, Peter H.L.; Hooijkaas, Ingeborg B.; van der Made, Ingeborg; de Gier-de Vries, Corrie; Wakker, Vincent; Creemers, Esther E.; de Laat, Wouter; Boukens, Bastiaan J.; Christoffels, Vincent M.
Abstract : Rationale: ANP (atrial natriuretic peptide) and BNP (B-type natriuretic peptide), encoded by the clustered genes Nppa and Nppb, are important prognostic, diagnostic, and therapeutic proteins in cardiac disease. The spatiotemporal expression pattern and stress-induction of the Nppa and Nppb are tightly regulated, possibly involving their coregulation by an evolutionary conserved enhancer cluster. Objective: To explore the physiological functions of the enhancer cluster and elucidate the genomic mechanism underlying Nppa-Nppb coregulation in vivo. Methods and Results: By analyzing epigenetic data we uncovered an enhancer cluster with super enhancer characteristics upstream of Nppb . Using CRISPR/Cas9 genome editing, the enhancer cluster or parts thereof, Nppb and flanking regions or the entire genomic block spanning Nppa-Nppb, respectively, were deleted from the mouse genome. The impact on gene regulation and phenotype of the respective mouse lines was investigated by transcriptomic, epigenomic, and phenotypic analyses. The enhancer cluster was essential for prenatal and postnatal ventricular expression of Nppa and Nppb but not of any other gene. Enhancer cluster–deficient mice showed enlarged hearts before and after birth, similar to Nppa-Nppb compound knockout mice we generated. Analysis of the other deletion alleles indicated the enhancer cluster engages the promoters of Nppa and Nppb in a competitive rather than a cooperative mode, resulting in increased Nppa expression when Nppb and flanking sequences were deleted. The enhancer cluster maintained its active epigenetic state and selectivity when its target genes are absent. In enhancer cluster–deficient animals, Nppa was induced but remained low in the postmyocardial infarction border zone and in the hypertrophic ventricle, involving regulatory sequences proximal to Nppa . Conclusions: Coordinated ventricular expression of Nppa and Nppb is controlled in a competitive manner by a shared super enhancer, which is also required to augment stress-induced expression and to prevent premature hypertrophy. Abstract : Supplemental Digital Content is available in the text.